Clinical, hematological, biochemical, and ultrasonographic aspects of platynosomum sp (trematoda: Dicrocoeliidae) infection of captive callithrix penicillata - Mattioli, Mariana Portugal; Dos Santos Batista, Juliana; Ferrari, Marlon; Paludo, Giane Regina; Dias, Cecília Azevedo; Hoppe, Estevam G. L. [UNESP]; Da Rocha, Gino Chaves; Monteiro, Rafael Veríssimo (Springer Nature, 2016)
Trematodes from the genus Platynosomum have been found to infect Neotropical primates in captivity, but little is known about their pathogeny in such hosts. This study evaluated the physiological effects of natural infection by the liver-dwelling trematode Platynosomum sp. in ten males and ten females of Callithrix penicillata kept in captivity at the Primate Center of the University of Brasília. The marmosets were examined twice, 6 months apart. The following parameters were analyzed: complete blood count, bleeding time, serum total protein, albumin, and the liver enzymes AST and ALT, and both a stool analysis and a liver ultrasonic evaluation were performed. We were able to characterize a group of abnormalities associated with this trematode infection which were mainly derived from the hepatitis caused by it: coagulation disorders, abnormal red blood cells, hypoalbuminemia, and abnormal levels of liver-linked serum enzymes. Eosinophilia and thrombocytopenia were also commonly seen. All of the aforementioned abnormalities were in good accord with typical effects of trematodes on liver parenchyma. We suggest that this set of abnormalities is characteristic of the infection of C. penicillata with Platynosomum sp., and should be among the most prominent aspects that the veterinary surgeon considers when suspecting such an infection. We also suggest that these clinical signs and abnormalities will be similar in other liver-dwelling trematode-infected primate species.
Keywords: Black-tufted marmoset; Health rank; Hepatic ultrasound; Liver disease; Trematode hepatopathy